ANALYSIS OF MORAL VALUE IN THE FILM "RAYA AND THE LAST DRAGON - Erminsah, Raka; Rosnija, Eni; Sumarni, Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe moral values contained in the Raya and The Last Dragon film. This research was conducted using a descriptive qualitative method because the data studied are in the form of language in the movie. The research method used was content analysis. The process of presenting the data in the form of table than the researches describe the utterence that contains the dialogue based on the movie. The source of the data was obtain from the movie transkip in Raya and The Last Dragon. The data were analyze, data collection and data analysis. The data of this research were 12 types of moral values. The finding showed that there were 12 types of moral values in this movie which consist individual moral values and sosial moral values, the first one is Honesty, Courage, Patience, Hard Work, Willing to Sacrifice, Humility, Responsibility, Never Quit, Cooperation, Kindness, Compassion, and Deliberation.